2008
DOI: 10.1186/1471-2458-8-92
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the tsunami disaster, PTSD symptoms and increased substance use – an Internet based survey of male and female residents of Switzerland

Abstract: Background: After the tsunami disaster in the Indian Ocean basin an Internet based self-screening test was made available in order to facilitate contact with mental health services. Although primarily designed for surviving Swiss tourists as well as relatives and acquaintances of the victims, the screening instrument was open to anyone who felt psychologically affected by this disaster. The aim of this study was to evaluate the influences between self-declared increased substance use in the aftermath of the ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 26 publications
8
57
1
Order By: Relevance
“…Further, the higher PTSD prevalence could have been caused by the use of a self-rating instrument to assess PTSD symptoms. In a Swiss internet-based study on tsunami victims [26] , the mean age of participants was most probably lower due to the digital divide in the use of internet technology.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the higher PTSD prevalence could have been caused by the use of a self-rating instrument to assess PTSD symptoms. In a Swiss internet-based study on tsunami victims [26] , the mean age of participants was most probably lower due to the digital divide in the use of internet technology.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics parallel the core clinical features of individuals with post-traumatic stress disorder (PTSD), i.e. reduced threshold of fear, impaired extinction of fear memory, vivid recall or flashbacks of traumatic memories and a high prevalence of cannabis abuse [23,36,49]. Despite the highest expression of cannabinoid receptors (CB 1 and CB 2 ) found in the cerebellum [20,25,48], its functional role remains to be established.…”
Section: Introductionmentioning
confidence: 97%
“…There have been conflicting findings regarding post-event outcomes (on the individual and community level) and antecedent risk factors. [6][7][8][9][10][11][12] The disaster literature has been growing quickly in the past decade, spanning studies evaluating physical as well as psychiatric/psychological outcomes following natural disasters and manmade disasters (e.g., terrorist activity) alike. For instance, in reviewing dozens of studies, Rodriguez et al found that although many persons are resilient in the face of exposure to disasters (with up to half of persons never developing symptoms), there is a vulnerable minority that may develop mood, anxiety, and posttraumatic stress disorder (PTSD) symptoms that persist for 18 months or more 13 depending on level of exposure and antecedent risk factors.…”
Section: Introductionmentioning
confidence: 99%